Restrictive strategy versus usual care for cholecystectomy in patients with gallstones and abdominal pain (SECURE): a multicentre, randomised, parallel-arm, non-inferiority trial. Issue 10188 (8th June 2019) - van Dijk, Aafke H; Wennmacker, Sarah Z; de Reuver, Philip R; Latenstein, Carmen S S; Buyne, Otmar; Donkervoort, Sandra C; Eijsbouts, Quirijn A J; Heisterkamp, Joos; Hof, Klaas in 't; Janssen, Jan; Nieuwenhuijs, Vincent B; Schaap, Henk M; et al.
Summary: Background: International guidelines advise laparoscopic cholecystectomy to treat symptomatic, uncomplicated gallstones. Usual care regarding cholecystectomy is associated with practice variation and persistent post-cholecystectomy pain in 10–41% of patients. We aimed to compare the non-inferiority of a restrictive strategy with stepwise selection with usual care to assess (in)efficient use of cholecystectomy. Methods: We did a multicentre, randomised, parallel-arm, non-inferiority study in 24 academic and non-academic hospitals in the Netherlands. We enrolled patients aged 18–95 years with abdominal pain and ultrasound-proven gallstones or sludge. Patients were randomly assigned (1:1) to either usual care in which selection for cholecystectomy was left to the discretion of the surgeon, or a restrictive strategy with stepwise selection for cholecystectomy. For the restrictive strategy, cholecystectomy was advised for patients who fulfilled all five pre-specified criteria of the triage instrument: 1) severe pain attacks, 2) pain lasting 15–30 min or longer, 3) pain located in epigastrium or right upper quadrant, 4) pain radiating to the back, and 5) a positive pain response to simple analgesics. Randomisation was done with an online program, implemented into a web-based application using blocks of variable sizes, and stratified for centre (academic versus non-academic and a high vs low number of patients), sex, and body-mass index. Physicians and patients were masked for study-arm allocation until after completion of the triage instrument. The primary, non-inferiority, patient-reported endpoint was the proportion of patients who were pain-free at 12 months' follow-up, analysed by intention to treat and per protocol. A 5% non-inferiority margin was chosen, based on the estimated clinically relevant difference. Safety analyses were also done in the intention-to treat population. This trial is registered at the Netherlands National Trial Register, number NTR4022. Findings: Between Feb 5, 2014, and April 25, 2017, we included 1067 patients for analysis: 537 assigned to usual care and 530 to the restrictive strategy. At 12 months' follow-up 298 patients (56%; 95% CI, 52·0–60·4) were pain-free in the restrictive strategy group, compared with 321 patients (60%, 55·6–63·8) in usual care. Non-inferiority was not shown (difference 3·6%; one-sided 95% lower CI −8·6%; pnon-inferiority =0·316). According to a secondary endpoint analysis, the restrictive strategy resulted in significantly fewer cholecystectomies than usual care (358 [68%] of 529 vs 404 [75%] of 536; p=0·01). There were no between-group differences in trial-related gallstone complications (40 patients [8%] of 529 in usual care vs 38 [7%] of 536 in restrictive strategy; p=0·16) and surgical complications (74 [21%] of 358 vs 88 [22%] of 404, p=0·77), or in non-trial-related serious adverse events (27 [5%] of 529 vs 29 [5%] of 526). Interpretation: Suboptimal pain reduction in patients with gallstones and abdominal pain was noted with both usual care and following a restrictive strategy for selection for cholecystectomy. However, the restrictive strategy was associated with fewer cholecystectomies. The findings should encourage physicians involved in the care of patients with gallstones to rethink cholecystectomy, and to be more careful in advising a surgical approach in patients with gallstones and abdominal symptoms. Funding: The Netherlands Organization for Health Research and Development, and CZ healthcare insurance.